Genetic analysis and prenatal diagnosis of short-rib thoracic dysplasia 3 with or without polydactyly caused by compound heterozygous variants of DYNC2H1 gene in four Chinese families - Fang, Yuying; Li, Shuo; Yu, Dongyi (Frontiers in Genetics, 2023)
Background: To describe the genetic variation of dynein cytoplasmic 2 heavy chain 1 (DYNC2H1) gene in four Chinese families affected with short-rib thoracic dysplasia 3 with or without polydactyly (SRTD3), and to provide evidence for accurate prenatal diagnosis and genetic counseling. Methods: The detailed clinical prenatal sonographic features of four fetuses with SRTD3 were carried out. Trio-whole exome sequencing (WES) and proband-WES sequencing was applied to filtrated causative variants in four families. The causative variants of each family were validated in by Sanger sequencing. Bioinformation analysis was applied to predict the harmfulness of these mutations and perform the protein-protein interaction network and Gene Ontology (GO) analysis. A vitro minigene splicing assay was conducted to assess the influence of the splice site variant. Results: Typical characterization of the four fetuses included short long bones, short ribs, narrow chest, hand and foot posture abnormalities, femur short in diameter and slightly bowing, cardiac abnormalities, and so on. Moreover, eight compound heterozygous variants of DYNC2H1 (NM_001080463.2): c.3842A>C (p.Tyr1281Ser) and c.8833-1G>A, c.8617A>G (p.Met2873Val) and c.7053_7054del (p.Cys2351Ter), c.5984C>T (p.Ala1995Val) and c.10219C>T (p.Arg3407Ter), c.5256del (p.Ala1753GlnfsTer13) and c.9737C>T (p.Thr3246Ile), were identified. Among which, c.10219C>T (p.Arg3407Terp), c.5984C>T (p.Ala1995Val) and c.9737C>T (p.Thr3246Ile) were reported in ClinVar databases, and c.8617A>G (p.Met2873Val), c.10219C>T (p.Arg3407Ter), c.5984C>T (p.Ala1995Val) were found in HGMD databases. Four variants (c.3842A>C (p.Tyr1281Ser), c.8833-1G>A, c.7053_7054del (p.Cys2351Ter) and c.5256del (p.Ala1753GlnfsTer13) were first reported as novel mutations. According to the ACMG guidelines, c.8617A>G (p.Met2873Val), c.7053_7054del (p.Cys2351Ter), c.5984C>T (p.Ala1995Val), c.10219C>T (p.Arg3407Ter) and c.5256del (p.Ala1753GlnfsTer13) were rated as pathogenic or likely pathogenic variants, others variants were predicted to be variants of uncertain significance mutations. The minigene assay results indicated that c.8833-1G>A caused the skipping over exon 56, resulting in exon 56 loss. Conclusion: In our study, we analyzed the genetic mutations in four fetuses with SRTD3 by whole exome sequencing and identified pathogenic variants causing SRTD3. Our results expand the mutation spectrum of DYNC2H1 in SRTD3, which is helpful for the accurate prenatal diagnosis of SRTD3 fetuses and provide useful strategies for genetic counseling.